2011
DOI: 10.1016/j.jacc.2010.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Iron Oxide Particles for In Vivo Magnetic Resonance Detection of Atherosclerotic Lesions With Antibodies Directed to Oxidation-Specific Epitopes

Abstract: Objectives The aim of this study was to determine whether iron oxide particles targeted to oxidation-specific epitopes image atherosclerotic lesions. Background Oxidized low-density lipoprotein plays a major role in atherosclerotic plaque progression and destabilization. Prior studies indicate that gadolinium micelles labeled with oxidation-specific antibodies allow for in vivo detection of vulnerable plaques with magnetic resonance imaging (MRI). However, issues related to biotransformation/retention of gad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
105
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 112 publications
(117 citation statements)
references
References 34 publications
12
105
0
Order By: Relevance
“…For example, MB47 detects not only the native apoB-100 moiety of unoxidized LDL but also apoB of minimally oxidized LDL and even apoB fragments of extensively oxidized LDL. MDA2 can recognize both MDA-LDL as well as MDA-lysine epitopes on other proteins in the vessel wall, such as apoAI ( 28,29 ), and it has also been utilized for noninvasive imaging of experimental atherosclerotic lesions (3)(4)(5). E06 is a well-characterized murine IgM natural antibody cloned from apoE Ϫ / Ϫ mice ( 20 ) that has previously been used to stain mouse and rabbit atherosclerotic lesions and to image atherosclerotic lesions in apoE Ϫ / Ϫ mice using magnetic resonance techniques (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, MB47 detects not only the native apoB-100 moiety of unoxidized LDL but also apoB of minimally oxidized LDL and even apoB fragments of extensively oxidized LDL. MDA2 can recognize both MDA-LDL as well as MDA-lysine epitopes on other proteins in the vessel wall, such as apoAI ( 28,29 ), and it has also been utilized for noninvasive imaging of experimental atherosclerotic lesions (3)(4)(5). E06 is a well-characterized murine IgM natural antibody cloned from apoE Ϫ / Ϫ mice ( 20 ) that has previously been used to stain mouse and rabbit atherosclerotic lesions and to image atherosclerotic lesions in apoE Ϫ / Ϫ mice using magnetic resonance techniques (3)(4)(5).…”
Section: Discussionmentioning
confidence: 99%
“…IK17 is a human Fab fragment derived from a phage display library, and it binds to a unique MDA-like epitope present on both MDA-LDL and copper-oxidized LDL. IK17 has also been used in detecting and imaging atherosclerosis in LDLR Ϫ / Ϫ mice and apoE Ϫ / Ϫ mice (3)(4)(5)22 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, within the time frame we studied, we found no significant accumulation of nontargeted nanoparticles in plaques. In addition, a report by Briley-Saebo et al (28) indicated that the intraplaque macrophage uptake of ∼35-nm iron oxide particles is limited by the ability of the particles to traverse through the arterial endothelial wall. Our results show that providing the nanoparticles with a LyP-1 coating overcomes this obstacle.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, apoptotic foam cells [133], oxidation-specific epitopes (malondialdehyde-lysine-epitopes of MDA-LDL [134]), oxidized phospholipid epitopes [134], scavenger receptors type A (with sulfated, dextran-coated SPIO) [135], VCAM-1 [136], E-and P-selectin [136], or oxidated LDL [137] in vulnerable and inflammatory plaques were able to be successfully labeled. In molecular myocardial infarction imaging, the use of MION-conjugated antimyosin-F ab (MION-R11D10) against myosin for labeling an infarcted myocardium is described [138].…”
Section: Cardiovascular Imagingmentioning
confidence: 99%